A Large Simulation Set of Geomagnetic Storms—Can Simulations Predict Ground Magnetometer Station Observations of Magnetic Field Perturbations?. Issue 11 (14th November 2022) - Al Shidi, Q.; Pulkkinen, T.; Toth, G.; Brenner, A.; Zou, S.; Gjerloev, J.
Abstract: We use the Space Weather Modeling Framework Geospace configuration to simulate a total of 122 storms from the period 2010–2019. With the focus on the storm main phase, each storm period was run for 54 hr starting from 6 hr prior to the start of the Dst depression. The simulation output of ground magnetic variations, Δ B H in particular, were compared with ground magnetometer station data provided by SuperMAG to statistically assess the Geospace model regional magnetic perturbation prediction performance. Our results show that the regional predictions at mid‐latitudes are quite accurate, but the high‐latitude regional disturbances are still difficult to predict. Plain Language Summary: Ground magnetic disturbances can cause spurious currents in power networks, natural gas pipelines, or other systems, and hence are a key target of space weather predictions. The ground magnetic disturbances produced by currents flowing in the ionosphere around 100 km as well as currents at higher altitudes. These currents are powered by complex processes related to the solar wind plasma and magnetic field interaction with the Earth's space environment. We use a large‐scale simulation of the Earth's space environment together with measurements of the ground magnetic field variations from over 100 stations around the world to statistically assess the model performance. Our results indicate that at the mid‐latitudes (e.g., over the continental U.S.), the model performance is quite good even at the regional scale, but at high latitudes near the Arctic Circle, the model performance is not as good. Key Points: Space Weather Modeling Framework (SWMF) simulations were carried out for 122 geomagnetic storms from 2010 to 2019 SWMF simulations of ground magnetic disturbances provide predictive results with a median Heidke Skill Score (HSS) of 0.45 for magnetometers in all regions Simulation performance for high‐latitude magnetic perturbations have lower HSS with a median of 0.32